2D Transition Metal Carbides (MXene) for Electrochemical Sensing: A Review. (19th May 2022) - Shahzad, Faisal; Zaidi, Shabi Abbas; Naqvi, Rizwan Ali
Abstract: MXene, a novel class of 2-dimensional transition metal carbides has evolved as a promising material for various applications owing to its outstanding characteristics such as hydrophilicity, high electrical conductivity, surface area, and attractive topological structure. MXenes can form dispersion in common solvents and constitute composite with other nanomaterials, which can be utilized as effective transducers for molecular sensing. MXene-modified support materials, thus provide an intriguing platform for immobilization of target molecules onto their surface. The literature reveals that it has been increasingly utilized in the sensing of diverse types of analytes including glucose, pharmaceuticals, metals and dyes, cancer markers, pesticides, neurotransmitters, small valuable molecules, and so on. In this review, we summarize the recent updates in the MXene modified materials for sensing. For the convenience of our audience, we have distributed the analytes into categories and discussed them comprehensively. Not only we present the synthesis approach, electrochemical properties and surface chemistry of MXenes but also discussed briefly the current challenges and an outlook for future research in the related area.